Ο απελευθερωτικός αγώνας και ο ελληνοκυπριακός τύπος. Οι θέσεις των εφημερίδων Ελευθερία, ο Φιλελεύθερος και Χαραυγή στην περιόδο 1955-1960 - Αντωνιάδης, Ευριπίδης (Τμήμα Επικοινωνίας και Σπουδών Διαδικτύου, Σχολή Επικοινωνίας και Μέσων Ενημέρωσης, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
Little is known about the relationship between the anticolonial movement in Cyprus and the role of the Greek-Cypriot press. This thesis aims to fill a small gap by presenting the preliminary findings of a study dealing with the Liberation Movement of Cyprus (EOKA) and how it was depicted through the Greek-Cypriot press. The period under study is 1955 to 1960, which is when the Liberation (EOKA) movement was active. This study investigates the positions of three leading Greek-Cypriot newspapers of that period and aims to present the positions of each newspaper at the level of policy towards the liberation movement. The study finds that each newspaper had its own political approach. Preliminary findings suggest that the Greek-Cypriot press under the colonial regime presented the liberation and the «Enosis» (unification) movement more in its news-articles-reports and less in opinion articles and commentaries, while journalists were reluctant to take sides.
Keywords: Press; Liberation Struggle; Colony; Cyprus; Απελευθερωτικό Κίνημα; Αποικία; ΕΟΚΑ; Κύπρος